A method for preparing an anion-doped halide solid-state electrolyte
Patent Information
- Application Number
- CN202511492627.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-10-17
AI Technical Summary
然而,以上类型的制备方式存在以下问题:①对金属氧化物的纯度和粒径要求较高;②副产物金属氯化物需要加热挥发去除,增加能耗,升温导致LACO材料结晶性增加,劣化材料性能,降低离子电导率和粘弹性,不利于该材料发挥进一步的优势
[0019]与现有技术相比,本发明具有以下优势:①原料易获取,价格低廉;②副产物常温常压下为气体或液体,不需要加热去除避免温度升高至结晶温度造成材料的结晶度上升,引起粘弹性降低和离子电导率降低。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage, and in particular to a method for preparing anion-doped halide solid electrolyte. Background Technology
[0002] Halide solid electrolytes are a novel type of high-performance electrolyte material. Their biggest difference from traditional liquid electrolytes is that they do not require a solvent; instead, they form a solid directly, making them more stable and safer. Furthermore, their conductivity and transport properties are higher than those of traditional liquid electrolytes. Halide solid electrolytes are widely used in electrochemical energy storage, solar cells, LEDs, supercapacitors, and other fields, with their application being most extensive in electrochemical energy storage.
[0003] electrolyte LiAlCl 4-2x O x (LACO, 0 < x < 2) is a type of halide solid electrolyte. Patent CN119153768B describes the synthesis of LACO solid electrolyte. Oxygen is introduced into the solid electrolyte by introducing antimony oxide or tin oxide into the raw materials. During ball milling, the heat and mechanical energy generated by the collision between the milling jar, millstone, and raw materials cause a solid-phase reaction, yielding a solid electrolyte precursor. Then, the metal elements in the metal oxide are removed by heating in the form of volatile chlorides, resulting in a viscoelastic solid electrolyte. Patent US20250210692A1 also mentions LACO. 75 Preparation of (i.e., x=0.75): LiAlCl4 and Sb2O3 are mixed, and a displacement reaction is induced between them by pressurization or heating: LiAlCl4 + x / 3Sb2O3 → LiAlCl4 4-2x O x +2x / 3SbCl3, the byproduct SbCl3 is a solid mixed in the electrolyte material at room temperature, and needs to be removed by heating to above 223℃ to obtain an electrolyte material with high ionic conductivity. However, the above preparation method has the following problems: ① It requires high purity and particle size of the metal oxide; ② The byproduct metal chloride needs to be removed by heating and volatilization, which increases energy consumption. The temperature rise leads to increased crystallinity of the LACO material, deteriorates the material performance, and reduces ionic conductivity and viscoelasticity, which is not conducive to the material exerting further advantages. Summary of the Invention
[0004] In view of this, the present invention provides a method for preparing anion-doped halide solid electrolyte. The method of the present invention can reduce costs, operates under mild conditions, and ensure the ionic conductivity and electrochemical performance of the electrolyte material.
[0005] This invention provides a method for preparing anion-doped halide solid electrolytes, comprising the following steps:
[0006] S1. Mix LiAlCl4 and ice and sequentially perform a first ball milling and a second ball milling to obtain ball-milled powder;
[0007] S2. The ball-milled powder is freeze-dried to obtain anion-doped halide solid electrolyte LiAlCl. 4- 2x O x , 0 < x < 2;
[0008] The first ball mill has a ball milling temperature of -20℃ to -5℃; the second ball mill has a ball milling temperature of 10℃ to 30℃.
[0009] Preferably, in step S1, the ball-to-material ratio of the ball mill is (1~10):1.
[0010] Preferably, in step S1, the rotational speed of the ball mill is 150~900 rpm.
[0011] Preferably, in step S1, the first ball milling time is 0.1~40h.
[0012] Preferably, in step S1, the molar ratio of LiAlCl4 to ice is 1:x, where 0 < x < 2.
[0013] Preferably, in step S2, the freeze-drying temperature is -60℃ to -40℃.
[0014] Preferably, in step S2, the vacuum degree of the freeze-drying is 13~26 Pa.
[0015] Preferably, in step S2, the freeze-drying time is 12-24 hours.
[0016] Preferably, in step S1, the ice is deionized ice.
[0017] Preferably, the deionized ice is obtained by freezing deionized water at low temperature.
[0018] The present invention provides a method for preparing anion-doped halide solid electrolytes, which is a low-temperature mechanical mixing method. First, LiAlCl4 and ice (i.e., solid H2O) are mixed and sequentially subjected to a first ball milling (milling temperature -20℃ to -5℃) and a second ball milling (milling temperature 10℃ to 30℃) to obtain ball-milled powder. Then, the ball-milled powder is freeze-dried to obtain the anion-doped halide solid electrolyte LiAlCl4. 4-2x O x(0 < x < 2). This invention selects H₂O as the substitution raw material to prepare LiAlCl₂. 4-2x O x Electrolyte material: Two raw materials are uniformly mixed in solid form using cryogenic ball milling. Then, the refrigeration is turned off, and ball milling continues naturally until the temperature rises, allowing the two raw materials to react and form LiAlCl. 4-2x O x Then, by freeze-drying to remove unreacted free water and hydrogen chloride that did not volatilize during ball milling, LiAlCl with high ionic conductivity can be finally obtained. 4-2x O x Electrolyte materials, and exhibit excellent electrochemical performance.
[0019] Compared with the prior art, the present invention has the following advantages: ① The raw materials are readily available and inexpensive; ② The by-products are gas or liquid at room temperature and pressure, and do not need to be removed by heating, thus avoiding the increase in crystallinity of the material caused by the temperature rising to the crystallization temperature, which leads to a decrease in viscoelasticity and ionic conductivity. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0021] Figure 1 The XRD patterns of the products obtained in Example 1 and Comparative Examples 7-8 of this invention are shown. Detailed Implementation
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0023] In this article, the technical features described in an open-ended manner include both closed technical solutions composed of the listed features and open technical solutions that include the listed features.
[0024] The term “and / or” as used herein includes any and all combinations of one or more of the related listed items.
[0025] In this document, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when a range refers to an integer, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0026] In this article, when referring to units for data ranges, if the unit is only followed by the right endpoint, it means that the units for the left and right endpoints are the same. For example, 150~900rpm means that the units for the left endpoint "150" and the right endpoint "900" are both rpm.
[0027] This invention provides a method for preparing anion-doped halide solid electrolytes, comprising the following steps:
[0028] S1. Mix LiAlCl4 and ice and sequentially perform a first ball milling and a second ball milling to obtain ball-milled powder;
[0029] S2. The ball-milled powder is freeze-dried to obtain anion-doped halide solid electrolyte LiAlCl. 4- 2x O x , 0 < x < 2;
[0030] The first ball mill has a ball milling temperature of -20℃ to -5℃; the second ball mill has a ball milling temperature of 10℃ to 30℃.
[0031] Regarding step S1 :
[0032] S1. Mix LiAlCl4 and ice and perform a first ball mill and a second ball mill in sequence to obtain ball-milled powder.
[0033] In this invention, the source of LiAlCl4 is not particularly limited; it can be a commercially available product or prepared according to methods known in the art.
[0034] In this invention, the ice is solid water, preferably deionized ice. The deionized ice can be prepared by freezing deionized water at low temperature. Preferably, the ice is pre-crushed; specifically, after obtaining deionized ice blocks by freezing deionized water at low temperature, the ice blocks are crushed to obtain crushed ice for subsequent use. The crushing method can be ball milling; the ball milling is carried out at a low temperature to keep the ice solid.
[0035] In this invention, after preparing LiAlCl4 and ice, the two are weighed. The molar ratio of LiAlCl4 to ice in this invention can be determined according to the stoichiometric ratio of the target product. Specifically, the molar ratio of LiAlCl4 to ice (i.e., solid H2O) is 1:x, where 0 < x < 2, and can be 0.1, 0.25, 0.4, 0.5, 0.75, 1, 1.8, etc., more preferably 0.75.
[0036] In this invention, after weighing, LiAlCl4 and ice are added to a mixing device for sequential first ball milling and second ball milling. The first ball milling is a low-temperature ball milling. Preferably, the mixing device is a low-temperature refrigerated ball mill, such as a liquid nitrogen type low-temperature ball mill, specifically a liquid nitrogen type refrigerated planetary ball mill. After adding LiAlCl4 and ice to the mixing device, the device is refrigerated for low-temperature ball milling. The temperature of the first ball milling is -20℃ to -5℃ to prevent premature melting of the ice and contact with LiAlCl4, which could cause the final product to deviate from the stoichiometric ratio. Specifically, the temperature can be -20℃, -19℃, -18℃, -17℃, -16℃, -15℃, -14℃, -13℃, -12℃, -11℃, -10℃, -9℃, -8℃, -7℃, -6℃, or -5℃. In this invention, the preferred ball-to-material ratio of the first ball mill is (1~10):1, specifically 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1. In this invention, the preferred rotational speed of the first ball mill is 150~900 rpm, specifically 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 880 rpm, or 900 rpm. In this invention, the preferred time for the first ball milling is 0.1 to 40 hours, specifically 0.1 hours, 0.5 hours, 1 hour, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours, 15 hours, 16 hours, 20 hours, 25 hours, 30 hours, 35 hours, or 40 hours.
[0037] In this invention, after the first ball milling, the cooling system of the mixing equipment is turned off, and ball milling continues until the temperature naturally rises to 10°C to 30°C. Here, turning off the cooling system refers to shutting down the cooling system of the ball milling equipment. The preferred rotational speed for the continued ball milling is 150 to 900 rpm, specifically 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, and 900 rpm, preferably consistent with the first ball milling stage. The ball mill is allowed to naturally heat to 10℃~30℃, specifically at temperatures of 10℃, 11℃, 12℃, 13℃, 14℃, 15℃, 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃, and 30℃. During this period, LiAlCl4 reacts with H2O as follows: LiAlCl4(s) + xH2O(l) → LiAlCl 4-2x O x (s) + 2xHCl(g). After the above treatment, ball milled powder is obtained.
[0038] This invention cools and solidifies liquid deionized water into ice, then breaks it down into fine particles. This achieves uniform contact between powders during the mixing process. Furthermore, by controlling certain ball milling conditions, the uneven distribution of ice during subsequent heating and melting prevents local components from deviating from the stoichiometric ratio, thereby obtaining a uniform and high-quality material.
[0039] Regarding step S2 :
[0040] S2. The ball-milled powder is freeze-dried to obtain anion-doped halide solid electrolyte.
[0041] In this invention, after obtaining the ball-milled powder in step S1, it is freeze-dried to remove unreacted free water. The freeze-drying temperature is preferably -60℃ to -40℃, specifically -60℃, -59℃, -58℃, -57℃, -56℃, -55℃, -54℃, -53℃, -52℃, -51℃, -50℃, -49℃, -48℃, -47℃, -46℃, -45℃, -44℃, -43℃, -42℃, -41℃, and -40℃. The freeze-drying is preferably vacuum freeze-drying, with a vacuum degree preferably between 13 and 26 Pa, specifically 13 Pa, 14 Pa, 15 Pa, 16 Pa, 17 Pa, 18 Pa, 19 Pa, 20 Pa, 21 Pa, 22 Pa, 23 Pa, 24 Pa, 25 Pa, and 26 Pa. The freeze-drying time is preferably 12-24 hours, specifically 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, and 24 hours. In this invention, after the above freeze-drying, the powder is preferably removed and placed in a dry environment to naturally rise to room temperature, yielding the anion-doped halide solid electrolyte product LiAlCl. 4-2x O x , 0 < x < 2. Where x can specifically be 0.1, 0.25, 0.4, 0.5, 0.75, 1, 1.8, etc.
[0042] In this invention, the preparation process of the above anion-doped halide solid electrolyte is preferably carried out in a dry room (dew point < -30°C).
[0043] The present invention provides a method for preparing anion-doped halide solid electrolytes, which is a low-temperature mechanical mixing method. First, LiAlCl4 and ice (i.e., solid H2O) are mixed and sequentially subjected to a first ball milling (milling temperature -20℃ to -5℃) and a second ball milling (milling temperature 10℃ to 30℃) to obtain ball-milled powder. Then, the ball-milled powder is freeze-dried to obtain the anion-doped halide solid electrolyte LiAlCl4. 4-2x O x (0 < x < 2). This invention selects H₂O as the substitution raw material to prepare LiAlCl₂. 4-2x O x Electrolyte material: Two raw materials are uniformly mixed in solid form using cryogenic ball milling. Then, the refrigeration is turned off, and ball milling continues naturally until the temperature rises, allowing the two raw materials to react and form LiAlCl. 4-2x O x Then, by freeze-drying to remove unreacted free water, LiAlCl with high ionic conductivity can be obtained. 4-2x O x Electrolyte materials, and exhibit excellent electrochemical performance.
[0044] Compared with existing technologies, this invention has the following advantages: ① H2O is readily available and inexpensive; ② The reaction byproduct HCl is a gas at room temperature and pressure (boiling point -85.1℃), which can be removed without heating, avoiding heating to LiAlCl. 4-2x O x Electrolyte performance deteriorates above the crystallization temperature.
[0045] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.
[0046] Example 1
[0047] S1. Deionized water was cryogenically frozen to obtain deionized ice, which was then ball-milled at -20°C using a cryogenic planetary ball mill. 27.86g of LiAlCl4 and 2.14g of deionized ice were weighed, with a molar ratio of 1:0.75, and the total weight of the raw materials was 30g. Both raw materials were added to a liquid nitrogen-type cryogenic planetary ball mill jar with a ball-to-material ratio of 5:1. The ball mill was cooled to -10°C by purging with liquid nitrogen and then ball-milled at 600 rpm for 6 hours. Afterward, the liquid nitrogen cooling was turned off, and ball-milling continued until the jar naturally warmed to 25°C, yielding the ball-milled powder.
[0048] S2. Place the ball-milled powder into a freeze dryer, cool it to -47℃ by passing liquid nitrogen through it, then apply a vacuum to 18 Pa and dry for 15 hours. Remove the powder and allow it to naturally warm to room temperature in a dry environment to obtain the finished product LiAlCl. 2.5 O 0.75 .
[0049] Example 2
[0050] The process was carried out according to Example 1, except that: ① the ball milling parameters were a ball-to-material ratio of 1:1, a temperature of -20°C, and a rotation speed of 880 rpm for 0.5 h; ② the freeze-drying parameters were a temperature of -53°C, a pressure of 21 Pa, and a drying time of 19 h; the other parameters were the same.
[0051] Example 3
[0052] The process was carried out according to Example 1, except that: ① the ball milling parameters were a ball-to-material ratio of 10:1, a temperature of -5℃, and a rotation speed of 350 rpm for 35 hours; ② the freeze-drying parameters were a temperature of -42℃, an air pressure of 15 Pa, and a drying time of 14 hours; the other parameters were the same.
[0053] Example 4
[0054] The process was carried out according to Example 1, except that: ① the ball milling parameters were a ball-to-material ratio of 7:1, a temperature of -10℃, and a rotation speed of 150 rpm for 40 hours; ② the freeze-drying parameters were a temperature of -58℃, a pressure of 24 Pa, and a drying time of 22 hours; the other parameters were the same.
[0055] Example 5
[0056] The procedure was carried out according to Example 1, except that: ① the molar ratio of LiAlCl4 to solid H2O was 1:0.1; ② the ball milling parameters were a ball-to-material ratio of 4:1, a temperature of -8℃, and a rotation speed of 650 rpm for 5 hours; ③ the freeze-drying parameters were a temperature of -45℃, a pressure of 17 Pa, and a drying time of 16 hours; the other parameters were the same.
[0057] Example 6
[0058] The procedure was carried out according to Example 1, except that: ① the molar ratio of LiAlCl4 to solid H2O was 1:0.25; ② the ball milling parameters were a ball-to-material ratio of 8:1, a temperature of -10℃, and a rotation speed of 600 rpm for 15 hours; ③ the freeze-drying parameters were a temperature of -49℃, a pressure of 19 Pa, and a drying time of 13 hours; the other parameters were the same.
[0059] Example 7
[0060] The procedure was carried out according to Example 1, except that: ① the molar ratio of LiAlCl4 to solid H2O was 1:0.4; ② the ball milling parameters were a ball-to-material ratio of 3:1, a temperature of -15℃, and a rotation speed of 550 rpm for 10 hours; ③ the freeze-drying parameters were a temperature of -55℃, a pressure of 23 Pa, and a drying time of 20 hours; the other parameters were the same.
[0061] Example 8
[0062] The procedure was carried out according to Example 1, except that: ① the molar ratio of LiAlCl4 to solid H2O was 1:0.5; ② the ball milling parameters were a ball-to-material ratio of 5:1, a temperature of -10℃, and a rotation speed of 600 rpm for 8 hours; ③ the freeze-drying parameters were a temperature of -41℃, a pressure of 14 Pa, and a drying time of 18 hours; the other parameters were the same.
[0063] Example 9
[0064] The procedure was carried out according to Example 1, except that: ① the molar ratio of LiAlCl4 to solid H2O was 1:1; ② the ball milling parameters were a ball-to-material ratio of 4:1, a temperature of -16℃, and a rotation speed of 700 rpm for 16 hours; ③ the freeze-drying parameters were a temperature of -50℃, a pressure of 20 Pa, and a drying time of 17 hours; the remaining parameters were the same.
[0065] Example 10
[0066] The procedure was carried out according to Example 1, with the following differences: ① The molar ratio of LiAlCl4 to solid H2O was 1:1.8; ② The ball milling parameters were a ball-to-material ratio of 5:1, a temperature of -8℃, and a rotation speed of 350 rpm for 4 hours; ③ The freeze-drying parameters were a temperature of -44℃, a pressure of 16 Pa, and a drying time of 21 hours; the remaining parameters were the same.
[0067] Comparative Example 1
[0068] The procedure was carried out according to Example 1, except that the ball milling temperature was 25°C, while the other parameters remained the same.
[0069] Comparative Example 2
[0070] The procedure was carried out according to Example 1, except that the ball milling temperature was -40°C, while the other parameters remained the same.
[0071] Comparative Example 3
[0072] The method was implemented according to Example 1, except that the ball-to-material ratio in the ball mill was 0.5:1, while the other parameters remained the same.
[0073] Comparative Example 4
[0074] The method was implemented according to Example 1, except that the ball-to-material ratio in the ball mill was 15:1, while the other parameters remained the same.
[0075] Comparative Example 5
[0076] The same as in Example 1 was implemented, except that the ball mill speed was 50 rpm, while the other parameters remained the same.
[0077] Comparative Example 6
[0078] The process was carried out according to Example 1, except that the ball milling time was 0.05 h, while the other parameters remained the same.
[0079] Comparative Example 7
[0080] The procedure was carried out according to Example 1, except that freeze drying was not used; instead, a forced-air drying oven was used to dry the material at 80°C for 5 hours.
[0081] Comparative Example 8
[0082] Using a conventional synthesis method, 21.21 g of LiAlCl4 and 8.79 g of Sb2O3 were weighed out with a molar ratio of 1:0.25. The mixture was mixed in a ball mill at room temperature with a ball-to-material ratio of 5:1 and a speed of 420 rpm for 2 hours. After mixing, the mixture was placed in a vacuum tube furnace and sintered at 250°C for 2 hours. After cooling, the mixture was ball-milled to obtain the final product.
[0083] The chemical formulas and operating parameters of the products of each embodiment and comparative example are shown in Table 1.
[0084] Table 1: Chemical formulas and operating parameters of the products from each example and comparative example
[0085]
[0086] Product Testing :
[0087] (1) Ionic conductivity test
[0088] The ionic conductivity of the powder products obtained in each embodiment and comparative example was tested at a temperature of 25°C. The test results are shown in Table 2.
[0089] Table 2: Ionic conductivity of each example and comparative product
[0090]
[0091] As can be seen from the test results in the table above, the ionic conductivity of the products obtained in Examples 1-10 of this invention is above 0.87 mS / cm, exhibiting high ionic conductivity. Among them, when x=0.75 (corresponding to Examples 1-4), the electrolyte LACO has the highest ionic conductivity, and at this doping concentration, the material structure possesses the optimal pathway for lithium-ion transport. At this doping concentration, the ionic conductivity using both cryogenic ball milling and freeze-drying processes is higher than 1.2 mS / cm, indicating that the process parameters given in this patent can effectively synthesize LACO solid electrolyte.
[0092] In Comparative Example 1, ball milling at room temperature caused the ice to melt rapidly, reacting before it could be uniformly mixed with LiAlCl4. This resulted in uneven oxygen ion doping, affecting the overall ionic conductivity of the material, which was only 0.48 mS / cm. In Comparative Example 2, the ball milling temperature was too low. In practice, it was found that excessively low ball milling temperatures caused severe LiAlCl4 ball adhesion to the mill walls, preventing uniform mixing and resulting in a low final ionic conductivity. In Comparative Example 3, the ball-to-material ratio was too low, leading to uneven mixing and a low final product ionic conductivity. In Comparative Example 4, the ball-to-material ratio was too high, leaving insufficient space for the grinding balls to move, deteriorating the mixing effect and hindering the reaction, also reducing ionic conductivity. In Comparative Example 5, the ball milling speed was too low, limiting the milling effect and preventing uniform mixing of the two raw materials, resulting in an unsatisfactory doping effect and deteriorated ionic conductivity. In Comparative Example 6, the ball milling time was too short, resulting in uneven mixing and a low ionic conductivity. Comparative Example 7 did not use freeze-drying but instead used conventional high-temperature drying. Because this material has a low crystallization temperature and low melting point, prolonged heating at high temperatures causes gradual crystallization, which is detrimental to lithium-ion transport, resulting in lower ionic conductivity compared to freeze-drying. Comparative Example 8 did not use freeze-ball milling or freeze-drying, but used conventional metal oxides as the oxygen source. Subsequent high-temperature heating removed the SbCl3 byproduct. The final product's ionic conductivity was significantly lower than that of the embodiments of this invention. This is because the high-temperature treatment increased the material's crystallinity, and the resulting structural changes hindered lithium-ion transport.
[0093] (2) XRD crystal diffraction test
[0094] XRD crystal diffraction tests were performed on the products obtained in Example 1 and Comparative Examples 7-8, and the results are as follows: Figure 1 As shown, the main phases of all three materials conform to the diffraction peak positions of PDF27-1210, but the peak intensity ratios of each diffraction peak differ. This is mainly because the crystal diffraction card library does not currently contain LiAlCl. 2.5 O 0.75 The standard card used was only LiAlCl2O (x=1), which has a similar structural composition, as a reference. Since the difference in composition manifests as different atomic arrangements on the same crystal plane, it causes changes in the diffraction peak intensity of the crystal plane, ultimately leading to changes in the relative peak intensity of the diffraction peaks. The XRD test results also show that the diffraction peak intensity of Example 1 is weaker than that of Comparative Examples 7 and 8. This is because both Comparative Examples 7 and 8 used heating to dry the material (Comparative Example 7) and remove by-products (Comparative Example 8), which increased the crystallinity of the product, resulting in increased diffraction peak intensity. Increased crystallinity degrades the ion transport performance of LACO, which is consistent with the ion conductivity test results.
[0095] (3) Assembly and testing of positive electrode mixed mold battery
[0096] ① Preparation of composite cathode materials
[0097] LACO was blended with high-nickel cathode (Ni83) using a planetary ball mill. The blending ratio was cathode:LACO:conductive agent SP mass ratio = 80:19.5:0.5, the ball-to-material ratio was 4:1, the ball milling speed was 420 rpm, and the ball milling time was 60 min. After the ball milling was completed, the composite cathode material was obtained.
[0098] ② Mold battery assembly
[0099] Weigh 0.1g of solid electrolyte Li6PS5Cl and place it in a ceramic sleeve. Fix both sides with positive and negative electrode posts. Pressurize it with 100MPa for 1min to form a sheet and fix it in the sleeve (sleeve inner diameter 10mm), which serves as the solid electrolyte layer of the mold battery. Weigh 18.3mg of the composite positive electrode material obtained in step ① and pour it into the sleeve. Compact it with the positive electrode post to obtain a dense positive electrode material layer. Then place a carbon-coated aluminum foil on the positive electrode material layer as the positive electrode current collector. Pressurize it with 300MPa for 2min using the positive electrode post to ensure a tight connection between the carbon-coated aluminum foil and the positive electrode material. Place an indium metal foil on the other side of the electrolyte layer. Flatten it with the negative electrode post and then place a copper-clad lithium sheet. The lithium metal side is in contact with the indium metal foil, and the copper-clad side is in contact with the negative electrode post. Apply 10MPa pressure and pressurize for 2min. Then remove the pressure and fix the ceramic sleeve and the positive and negative electrode posts with screws and nuts to obtain the mold battery.
[0100] ③ Electrochemical testing
[0101] The charge / discharge specific capacity (mAh / g) and discharge capacity retention (%) at 0.1C, 0.5C, and 1C rates were tested respectively. The test temperature was 25℃, the test voltage was 2~3.7V, the charge / discharge rate was the same, and each rate was cycled 5 times. The specific capacity data of the first cycle at each rate was selected as the test data. The test results are shown in Table 3.
[0102] Table 3: Test Results of Cathode Hybrid Batteries
[0103]
[0104] As can be seen from the test results in the table above, compared with the comparative example, the embodiment has significant advantages in charge-discharge specific capacity, efficiency, and discharge capacity retention at different rates. The main reasons are: ① The use of low-temperature ball milling and low-temperature drying results in lower material crystallinity. Its disordered structure is conducive to lithium ion transport and achieves higher ionic conductivity, thus improving the rate performance of the battery, which is reflected in higher discharge specific capacity at high rates; ② The low crystallinity further reduces the Young's modulus of the material and enhances its viscoelastic properties. It mixes more uniformly with the cathode particles and has better interfacial contact performance, which is conducive to lithium ion transport during charge and discharge. Combined with high ionic conductivity, it can improve the overall performance of the cathode material, resulting in improved specific capacity, coulombic efficiency, and rate performance.
[0105] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.
Claims
1. A method for preparing anion-doped halide solid electrolyte, characterized in that, Includes the following steps: S1. Mix LiAlCl4 and ice and sequentially perform a first ball milling and a second ball milling to obtain ball-milled powder; S2. The ball-milled powder is freeze-dried to obtain anion-doped halide solid electrolyte LiAlCl. 4-2x O x , 0 < x < 2; The ball milling temperature of the first ball mill is -20℃ to -5℃; the ball milling temperature of the second ball mill is 10℃ to 30℃. The molar ratio of LiAlCl4 to ice is 1:x, where 0 < x < 2; The above preparation process of anion-doped halide solid electrolytes was carried out in a dry room with a dew point of < -30℃.
2. The preparation method according to claim 1, characterized in that, In step S1, the ball-to-material ratio of the ball mill is (1~10):
1.
3. The preparation method according to claim 1, characterized in that, In step S1, the rotation speed of the ball mill is 150~900 rpm.
4. The preparation method according to claim 1 or 3, characterized in that, In step S1, the first ball milling time is 0.1~40h.
5. The preparation method according to claim 1, characterized in that, In step S2, the freeze-drying temperature is -60℃ to -40℃.
6. The preparation method according to claim 1, characterized in that, In step S2, the vacuum degree of the freeze-drying is 13~26 Pa.
7. The preparation method according to claim 1, characterized in that, In step S2, the freeze-drying time is 12-24 hours.
8. The preparation method according to claim 1, characterized in that, In step S1, the ice is deionized ice.
9. The preparation method according to claim 8, characterized in that, The deionized ice is obtained by freezing deionized water at low temperature.
Citation Information
Patent Citations
A solid electrolyte, a composite positive electrode and a preparation method thereof, and an ultra-fast charging all-solid-state battery
CN119153768B
Inorganic Glass Composite Solid Electrolytes for Lithium or Sodium Batteries
US20250210692A1
Preparation method of inorganic solid electrolyte
CN117602665A
Electrolyte for Electrochemical Battery Cell and Battery Cell Containing the Electrolyte
US20140220428A1